Digital electronics with VHDL - Kleitz, William, ....- (Upper saddle River : Pearson, 2004)
1. Number Systems and Codes. 2. Digital Electronic Signals and Switches. 3. Basic Logic Gates. 4. Programmable Logic Devices- CPLDs and FPGAs with VHDL Design. 5. Boolean Algebra and Reduction Techniques. 6. Exclusive-OR and Exclusive-NOR Gates. 7. Arithmetic Operations and Circuits. 8. Code Converters, Multiplexers, and Demultiplexers. 9. Logic Families and Their Characteristics. 10. Flip-Flops and Registers. 11. Practical Considerations for Digital Designs. 12. Counter Circuits and VHDL State Machines. 13. Shift Registers. 14. Multivibrators and the 555 Timer. 15. Interfacing to the Analog World. 16. Semiconductor, Magnetic, and Optical Memory. 17. Microprocessor Fundamentals. 18. The 8051 Microcontroller. Appendix A- WWW Sites. Appendix B- Manufacturers' Data Sheets. Appendix C- Explanation of the IEEE/IEC Standard for Logic Symbols (Dependency Notation). Appendix D- Answers to Odd-Numbered Problems. Appendix E- VHDL Language Reference. Appendix F- Review of Basic Electricity Principles. Appendix G- Schematic Diagrams for Chapter-End Problems. Appendix H- 8051 Instruction Set. Index. Supplementary Index of ICs.
Keywords: Digitale technieken ; VHDL